Terapi Rumatan Metadona di UPT. Puskesmas Kuta I - Ni Ketut Yudiasih; I W Artana; I Dewa Agung Gde Fanji Pradiptha (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2020)
ABSTRACTBackground of Study: The use of injecting drug is one of the HIV transmission media in Indonesia. From P2P Department Kemenkes RI data, the percentage of risk factors causing HIV / AIDS include injecting drug users as much as 8.4%. So the government developed PMMT. The purpose of this study is to understand the reasons for someone using injecting narcotics and the process of implementing MMT in IUS Kuta I Public Health Center.Methods : The research design used was qualitative interpretative paradigm, and the theory used was the phenomenology of Alfred Schutz and AGIL Talcott Persons. The data analysis used was the Mile Huberman interactive model, to check the validity of the findings using triangulation of data collection techniques.Results : The results found there were several reasons a person used injecting narcotics (heroin/morphine) including reasons for offers from friends, the environment, deviant behavior, and lack of knowledge. While the findings related to the implementation of methadone maintenance therapy at IUS Kuta I Public Health Center that the process of implementing the MMT was the procedure for the administration of the take-home dose (THD) more than three doses or 500 mg, the patient does not follow the rules of closing the ticket window (12.00 P.M.) and MMT services, the referral procedure for foreigners to get services.Conclusion : In this research, the process of implementing MMT has deviated from Talil Persons' AGIL theory and to service users to follow national guidelines and SOPs that have been set by local policy holders.Keywords : Injecting Drug (heroin/morfin), Methadone Maintenance Therapy (MMt)